Survey of accounting / Thomas P. Edmonds, University of Alabama-Birmingham, Christopher T. Edmonds, University of Alabama-Birmingham, Philip R. Olds, Virginia Commonwealth University, Frances M. McNair, Mississippi State University, Bor-Yi Tsay, Kennesaw State University. - Edmonds, Christopher T.
Includes index.